1996
DOI: 10.1038/ng1296-482
|View full text |Cite
|
Sign up to set email alerts
|

Identification of BTG2, an antiproliferative p53–dependent component of the DNA damage cellular response pathway

Abstract: Cell cycle regulation is critical for maintenance of genome integrity. A prominent factor that guarantees genomic stability of cells is p53 (ref. 1). The P53 gene encodes a transcription factor that has a role as a tumour suppressor. Identification of p53-target genes should provide greater insight into the molecular mechanisms that mediate the tumour suppressor activities of p53. The rodent Pc3/Tis21 gene was initially described as an immediate early gene induced by tumour promoters and growth factors in PC12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
337
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(352 citation statements)
references
References 32 publications
14
337
1
Order By: Relevance
“…BTG2, which was down-regulated in our tumors, is another gene with p53-dependent expression that may be relevant to cell cycle control and cellular response to DNA damage. 25 CHES1 is a member of the fork head/Winged Helix family of transcription factors, which sup- presses a number of DNA damage-activated checkpoint mutations in Saccharomyces cerevisiae. 26 Recently, mutations in checkpoint kinase 2 (CHK2), whose activation in response to DNA damage prevents cellular entry to mitosis, has been suggested as a tumor suppressor gene conferring predisposition to sarcomas, breast cancer and brain tumors in Li-Fraumeni syndrome.…”
Section: Genes Related To Growth Regulation/apoptosismentioning
confidence: 99%
“…BTG2, which was down-regulated in our tumors, is another gene with p53-dependent expression that may be relevant to cell cycle control and cellular response to DNA damage. 25 CHES1 is a member of the fork head/Winged Helix family of transcription factors, which sup- presses a number of DNA damage-activated checkpoint mutations in Saccharomyces cerevisiae. 26 Recently, mutations in checkpoint kinase 2 (CHK2), whose activation in response to DNA damage prevents cellular entry to mitosis, has been suggested as a tumor suppressor gene conferring predisposition to sarcomas, breast cancer and brain tumors in Li-Fraumeni syndrome.…”
Section: Genes Related To Growth Regulation/apoptosismentioning
confidence: 99%
“…Among these are p21 (el-Deiry et al, 1993), GADD45 (Kastan et al, 1992), BAX (Miyashita et al, 1994), MDM2 (Wu et al, 1993), BTG2 (Rouault et al, 1996), PIGs ), 14-3-3s (Hermeking et al, 1997, IGFBP3 (Buckbinder et al, 1995), PI(3)K regulatory subunit p85 (Yin et al, 1998), KILLER/DR5 , and TAP I (Zhu et al, 1999). p21, 14-3-3s, GADD45, and BTG2 have been shown to be capable of mediating p53-dependent cell cycle arrest (Chen et al, 1996;elDeiry et al, 1993;Hermeking et al, 1997;Rouault et al, 1996;Wang et al, 1999) while BAX, p85, IGFBP3, KILLER/DR5 and PIGs may mediate apoptosis (Buckbinder et al, 1995;Miyashita et al, 1994;Polyak et al, 1997;Wu et al, 1997;Yin et al, 1998). Recently, we found that TAP1 is speci®cally induced by both p53 and p73, which leads to enhanced transport of MHC class I peptides, suggesting that tumor surveillance can be mediated by the p53 family tumor suppressor proteins (Zhu et al, 1999).…”
mentioning
confidence: 99%
“…The tob gene, together with the btg1 and pc3/tis21/ btg2 genes, forms a new antiproliferative gene family (Matsuda et al, 1996;Rouault et al, 1992Rouault et al, , 1996Bradbury et al, 1991;Fletcher et al, 1991). Both the BTG1 and Tob proteins suppress growth of NIH3T3 cells when overexpressed (Matsuda et al, 1996;Rouault et al, 1992).…”
mentioning
confidence: 99%